Congenital methemoglobinemia. Report of a case - Zárate Aspiros Romeo; Rosas Sumano Ana Beatriz; Sánchez Ramírez Alma Rosa (Acta Pediátrica de México, 2014)
Methemoglobinemia is a condition in which there are high blood levels of methemoglobin. It may be congenital or acquired. The congenital form (which is rare) is the result of a defect in the methemoglobin reductase enzyme, dependent of the nicotinamide adenine dinucleotide phosphate reduced (NADPH); it is also caused by hemoglobinopathies. Congenital methemoglobinemia type 2 constitutes 10% of all cases and is usually fatal in early life. Its main feature is progressive neurological deterioration associa- ted with mental retardation, microcephaly, opisthotonos, athetotic movements, and generalized hypertonia. We report the case of a newborn with cyanosis from birth in whom perinatal hypoxia, pulmonary disease, heart failure and sepsis were ruled out, hence methemoglobin levels were requested, which led to the diagnosis of congenital methemoglobinemia based on a methemoglobin of 29.6%. Methemoglobin values were investigated in his 2 years old brother, who was cyanotic and showed progressive psychomotor retardation from birth; his methemoglobin was 30%. We concluded that both patients had type 2 hereditary methemoglobinemia in view of the severe neu- rological disorders of the older brother. Treatment with ascorbic acid was initiated in both siblings, resulting in the disappearance of cyanosis in the newborn.